Prevalence of Parasitic Infections with Zoonotic Potential in Tilapia: A Systematic Review and Meta-Analysis - Víctor Johan Acosta-Pérez; Juan Carlos Ángeles-Hernández; Vicente Vega-Sánchez; Andrea Paloma Zepeda-Velázquez; Javier Añorve-Morga; Jesús Benjamín Ponce-Noguez; Nydia Edith Reyes-Rodríguez; Jorge Luis De-La-Rosa-Arana; José Gustavo Ramírez-Paredes; Fabián Ricardo Gómez-De-Anda (Animals, 2022)
Tilapia has a high socioeconomic value in many countries worldwide. However, it has been identified as a zoonotic parasite reservoir. A systematic literature search and meta-analysis were carried out in order to estimate the global prevalence of zoonotic parasites that affect tilapia. The search was performed by three field experts to avoid reviewer bias. Polled prevalence was estimated using a logistic-normal random-effect regression model in the R software. We dealt with the heterogeneity among studies through subgroup analysis, taking into account the continent, country, genus of the host, parasite taxonomic group, sample origin, and type of diagnostic test as moderator variables. Fifty-two eligible articles were identified covering five tilapia genera with a pooled prevalence of 0.14 (95% CI: 0.10–0.20) showed significant heterogeneity (I2 = 98.4; p < 0.001). The subgroup analysis revealed that the most affected host was Sarotherodon, with a prevalence of 0.42 (95% CI: 0.22–0.65). Cestode was the taxonomic group with the largest prevalence (0.40; 95% CI:0.32–0.48), followed by amoeba (0.24; 95% CI: 0.16–0.35) and nematode (0.22; 95% CI: 0.11–0.38), among which, Schyzocotyle spp., Opistorchis spp., Gnathostoma spp. and Vermamoeba spp. have an impact on public health. Significant differences (p < 0.004) were found among continents and countries, with the highest value of prevalence detected in the African continent (0.28; 95% CI: 0.20–0.37), specifically in Tanzania (0.56; 95% CI: 0.22–0.87) and Egypt (0.43; 95% CI: 0.20–0.55). The origin of samples had a significant effect (p < 0.0001) on the detected prevalence, especially from those that showed the highest prevalence (0.24; 95% CI: 0.17–0.33). Finally, there were no differences in prevalence according to the diagnostic test (p = 0.97). Our results provide useful information on the development of epidemiological programs for the control of zoonoses associated with parasites in tilapia and in the design, planning, and implementation of future research.